Morphological Characterization of Mycobacterium tuberculosis in a MODS Culture for an Automatic Diagnostics through Pattern Recognition - Alva, A (2013)
The initial development of the algorithm was funded by a Wellcome Trust Career Development Fellowship awarded to DAJM [078067/Z/05] and by the Peruvian FINCYT Proyecto de Interes Nacional [PIN 061] and CONCYTEC PROCYT awarded to MZ. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.